Innovative Technique for Mechanized Underwater Welding of High-Alloy Corrosion-Resistant Steel - Kakhovskyi, M.Yu. (Science and Innovation, 2024)
The welding-repair technique using self-shielding flux-cored wire for underwater welding of high-alloy stainless steels of 18-10 type has been described. Its application enables minimizing the human intervention in the welding process under extreme conditions. The technique allows the welders to do repair works directly under water, without any additional assembly works.